Scaling Readiness: an evidence-based approach to co-design, implement and monitor scaling strategies for innovation teams and innovation portfolio managers. - Schut, Marc; Sartas, Murat; Leeuwis, Cees; Dror, Iddo (CGIAR System Organization, 2024)
Scaling Readiness: an evidence-based approach to co-design, implement and monitor scaling strategies for innovation teams and innovation portfolio managers.